2017
DOI: 10.1038/s41598-017-18114-2
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic enhancing effect for mechanical and electrical properties of tungsten copper composites using spark plasma infiltrating sintering of copper-coated graphene

Abstract: Successful applications of WCu alloys in high voltage electrical switches require their high strength and excellent conductivity. Unfortunately, the strategies for increasing their strength such as doping with fine particles and alloying often significantly decrease their conductivity. In this paper, we developed a new pathway for fabricating WCu alloys using spark plasma infiltrating sintering of copper-coated graphene (Cu@Gr) composite powders. Cu@Gr was found to partially prevent the formation of WC after s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
35
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(37 citation statements)
references
References 31 publications
2
35
0
Order By: Relevance
“…It can be seen that the graphene is made up of a wrinkled and folded membrane. From Figure 9b, the graphene sheets are stacked and agglomerated, probably due to the fact that the monolayer nickel-coated graphene sheets are not completely dried before bonded with the graphene layer, which has also been reported in the literature [16]. EDS elemental mapping of the Ni@graphene is shown in Figure 9c,d.…”
Section: Resultssupporting
confidence: 57%
See 1 more Smart Citation
“…It can be seen that the graphene is made up of a wrinkled and folded membrane. From Figure 9b, the graphene sheets are stacked and agglomerated, probably due to the fact that the monolayer nickel-coated graphene sheets are not completely dried before bonded with the graphene layer, which has also been reported in the literature [16]. EDS elemental mapping of the Ni@graphene is shown in Figure 9c,d.…”
Section: Resultssupporting
confidence: 57%
“…An efficient method was proposed to pre-coat the surface of graphene with a layer of metal in order to prevent its agglomeration in the matrix [15,16]. Due to the improved dispersion and good interfacial bonding, thermal energy and electrons can be effectively transferred between graphene and the coated metal and thus the wettability of metal-coated graphene can be significantly improved.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, graphene has been widely used as an excellent reinforcement material for metal matrix composites (MMCs). Previous studies showed remarkable achievements in mechanical properties of Al, Cu, Mg and WCu matrix composites after reinforced with graphene [5][6][7][8][9][10]. For example, tensile strength of Cu matrix composites with an addition of 2.5 vol.% reduced graphene oxide (rGO) prepared by molecule level mixing and spark plasma sintering (SPS) reached up to 748 MPa [11].…”
Section: Introductionmentioning
confidence: 99%
“…However, W–Cu composites prepared by liquid-phase sintering or infiltration exhibit inferior compositional uniformity and an undesirable contradiction between density and grain size due to the significant difference in melting points of W and Cu [ 4 , 5 ]. It has been reported that the reduction in the size of W particles or the addition of a small amount of nano-W powder can improve the hardness and conductivity of W–Cu composites [ 6 , 7 , 8 ]. However, with the decrease of W grain size, it is difficult to balance densification and microstructural uniformity.…”
Section: Introductionmentioning
confidence: 99%